La Crisis de 1914-1924 y el Sector Fabril en Chile - Ortega-Martinez, L (2012)
The First World War delivered a severe blow to the already unstable Chilean economy and inaugurated a long and protracted critical period, which ended only in the mid 1930s. Which not only caused the collapse of the export sector, but it also meant an end to the very foundations of the growth "model" that had been implemented since the 1830s. The decision made by the Chilean leadership after the War of the Pacifi c (in the early 1880s) to transform the country into a mono-export economy is one of the factors that explain the chaotic postwar situation- insofar as the country became exposed and vulnerable to the ups and downs of the international economy. Yet most of the economic troubles were created domestically, particularly by the economic policies implemented both by Congress and the government. But while external factors (World War One in particular) created incentives for import substitution, the management of the economy created obstacles, which were only removed after the political crisis of 1924 that signaled the beginning of the end of the traditional order. In that context, the necessity to develop the manufacturing industry gradually became an option for the country s development and growth. This process was carried out by the middle class and became consolidated by the mid 1920s.